2021
DOI: 10.3390/ma14061362
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of High Performance Synchronous Grouting Materials Prepared with Clay

Abstract: Shield construction discharges a large amount of soil and muck. The utilization of discharged soil of shield always has high energy consumption and a low utilization rate. Meanwhile, synchronous grouting is a key process for shield tunneling. The current studies show that the synchronous grouting materials applied now generally have the problem of mismatching among filling property, fluidity, and consolidation strength. In order to study the feasibility of using the excavated soil produced by shield constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…e reaction between OPC and steel slag is based on breaking Si-O, Al-O, and Ca-O bonds inside vitreous steel slag by OH-ions, which leads to the formation of CSH-like products [25]. When calcium hydroxide is consumed in this reaction, the durability and compressive strength of hardened sample are enhanced [28,55]. is is the mechanism by which steel slag improves the mechanical properties in the OPC-steel slag-waste sediment system.…”
Section: Mechanism Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e reaction between OPC and steel slag is based on breaking Si-O, Al-O, and Ca-O bonds inside vitreous steel slag by OH-ions, which leads to the formation of CSH-like products [25]. When calcium hydroxide is consumed in this reaction, the durability and compressive strength of hardened sample are enhanced [28,55]. is is the mechanism by which steel slag improves the mechanical properties in the OPC-steel slag-waste sediment system.…”
Section: Mechanism Discussionmentioning
confidence: 99%
“…Waste sediment has been used instead of water and bentonite to prepare the grouting material. It was found that the layering degree and bleeding rate of the synchronous grouting slurry prepared with waste sediment were significantly reduced, which solved the pumping problem occurring during grouting [27,28]. e initial fluidity of the grouting material is about 230 mm, and the 28-day compressive strength is greater than 2.5 MPa, meeting the property requirement in the grouting field [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Five commercially available epoxy resin grouting materials were selected for evaluation, as specified in Table 1. The epoxy grouting material is required to penetrate into the rock body to enhance its hardness, thus necessitating a penetration depth test [23][24][25][26]. Due to the loose nature of the rock bodies in faults F2 and F3, they tend to disperse when soaked in water.…”
Section: Methodsmentioning
confidence: 99%
“…Further, bentonite caused the increased viscosity and the decreased fluidity of grouts. Cui et al [15] studied that the addition of waterborne epoxy resin can improve the fluidity and reduce the density of the grouts.…”
Section: Introductionmentioning
confidence: 99%